BUFFALO SPERMATOZOA CLASSIFIED BASED ON PLASMALEMMA FUNCTIONAL INTEGRITY AND ACROSOMAL INTEGRITY TESTS - SELVARAJU, S; RAVINDRA, J P; PRATAP, N; PRASAD, B ARUN; RENUKARYADHYA, G J; ARORA, V K (The Indian Journal of Animal Reproduction, 2023)
The aim of this study was to assess the plasmalemma functional integrity and acrosomal integrity and their relationship with sperm functional tests in assessing buffalo semen quality. Fifty-two ejaculates from thirteen Murrah buffalo bulls were used for the study. Plasmalemma integrity and acrosomal integrity was assessed byfluorogenic and hypoosmotic swelling- Giemsa (HOS-G) test. The samples were classified into different subpopulations based on their reaction to fluorogenic staining and HOSG test, respectively. No difference in plasmalemma integrity (%) was observed (49.11±2.53 vs. 48.59±2.48) between fluorogenic and HOS-G tests. However, the acrosomal integrity(%) assessed by HOS-G test (82.43±4.15) was significantly higher (P<0.05) than fluorogenic stain (68.12±3.03). The sperm subpopulation (%) positiv for plasmalemma integrity and acrosornal integrity (P+A+) was significantly (P<O .0 5) higher in fluorogen ic (49 .11±2. 53) than H OS-G ( 43 .08±2. 3 8) tests. Further, the plasmalemma functional membrane integrity (48.59±2.48 %) was significantly higher than the sperm p• A· subpopulation ( 43. 08±2 .38 % ) . In the p• A• subpopulation, significant correlation (r"’ 0 .529, P<O. 05) was observed between fluorogenic and HOS-G test. The sperm p•N subpopulation had a significant positive correlation with the progressive forward motility (r=0.733, fluorogenic; r:::0.666, HOS-G), acrosomal integrity (r"’0.844, fluorogenic; r=0.569, HOS-G) and sperm nuclear morphology (r=0.617, fluorogenic; r=0.752, HOS-G). The study confirmed that fluorogenic and HOS-G tests n:ieasure the functional membrane integrity. It can be concluded that the assessing f sperm P•A• subpopulation by HOS-G test is easy and simple and can be recommended as a routine test to evaluate buffalo semen quality.